(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2020)
Finite element (FE) method is presented for the analysis of thin rectangular laminatedcomposite decks plates under the biaxial action of in – plane compressive loading. Theanalysis uses the classical laminated plate theory (CLPT) which does not account for sheardeformations. In this theory it is assumed that the laminate is in a state of plane stress, theindividual lamina is linearly elastic, and there is perfect bonding between layers. The classicallaminated plate theory (CLPT), which is an extension of the classical plate theory (CPT)assumes that normal to the mid – surface before deformation remains straight and normal tothe mid – surface after deformation. Therefore, this theory is only adequate for bucklinganalysis of thin laminates. A Fortran program has been developed. New numerical results aregenerated for in – plane compressive biaxial buckling which serve to quantify the effect ofboundary conditions on buckling loading. It is observed that, for all cases the buckling loadincreases with the mode number but at different rates depending on whether the plate is simplysupported, clamped or clamped – simply supported. The buckling load is a minimum whenthe plate is simply supported and a maximum when the plate is clamped. Because of therigidity of clamped boundary condition, the buckling load is higher than in simply supportedboundary condition. It is also observed that as the mode number increases, the plate needsadditional supp